Percutaneous transluminal coronary angioplasty in the right ventricle myocardial infarction treatment - Rafajlovski Saša I.; Orozović Vjekoslav; Ristić-Anđelkov Anđelka; Rađen Goran (Vojnosanitetski Pregled)
Background/Aim. To present the results of percutaneous transluminal coronary angioplasty (PTCA) in the treatment of the patients with acute right ventricle myocardial infarction (ARVMI), with adjuvant analyses of the obtained results in the period of five years (2000-2004). Methods. Thrombolytic therapy and the primary percutaneous transluminal coronary angioplasty (PPTCA) was applied within the first 6 hours from the onset of anginous disorders, and rescue PTCA in the period from 6−24 hours from the onset of ARVMI. Results. A total number of 1175 patients, both sexes, 763 (64.8%) males and 412 females (35.2%), mean age 58.4 ± 7.8 years, were treated for acute myocardial infarction (AIM) of different localization in the period of five years (2000-2004). Anterior infarction was found in 645 (54.8%) of the patients, and inferoposterior infarction (IPI) was localized in 530 patients (45.2%) patients of which in 134 (25.2%) AIMDK was proven. Out of 134 patients with proven acute myocardial of the right ventricle AIMDK, 53 (39.5%) got thrombolytic therapy, 64 patients (47.7%) were treated with the conservative heparin therapy, whereas in 17 patients (12.8%), primary percutaneous coronary angioplasty (PPTCA) was done. Delayed or rescue PTCA was done in 22 (18.8%) patients, in 8 (36.3%) from the group which got thrombolytic therapy, and in 14 (63.7%) treated with the heparin therapy. Out of the total number of 22 patients who got heparin or thrombolytic therapy combined with rescue PTCA, in 7 patients (31.8%) the complete clinical and angiographic effect of thrombolysis with AIM was achieved only by using a balloon. Baloon dilatation with the implantantion of intracoronary stent was performed in another 11 patients (50%), while 2 (9.1%) were sent to revascularization of the myocard due to diffusion changes in each of the 3 blood vessels, and 2 patients (9.1%) died. Of the patients, 17 (12.6%) had PPTCA with the implantation of intracoronary stent with the additional direct inhibitor of the platelet membrane glycoproteins IIb/IIIa (abciximab). All the patients treated in this way survived. They had no side effects nor serious complications. Their clinical recovery was satisfactory. In the first three weeks of the intrahospital period in the group of 45 patients (33.5%) with AIMDK, who got only thrombolytic therapy, 7 patients (15.5%) died, whereas in the group of 50 patients (37.3%) treated only with heparin, 13 (26%) died. In the group of 22 patients (18.8%) treated with the combined therapy with rescue PTCA and heparin or thrombolytic therapy, 2 patients (9.1%) died. In the group of 84 patients (62.6%) with AIMDK, who were treated with thrombolytic therapy with primary or rescue PTCA, 9 (10.7%) died. In the AIMDK group of 134 patients, 22 patients (16.4%) died in the period of 1 month of the hospital treatment, whereas in the second group of 396 patients with IPI, but without IDK, 36 (9.1%) died (χ2 = 4.789; p < 0.001). Out of the total number of 1175 patients with AIM in the five-year period of the intrahospital treatment, 145 patients (12.3%) died. In the group of patients with IPI, 58 patients out of 530 (10.9%) died, whereas 87 patients out of 645 (13.4%) with anterior infarction died, (χ2 = 0.567; p < 0.452). Conclusion. The combination of thrombolytic therapy and PTCA shown in the obtained results completely justified this kind of treatment, and offered the patients with AIMDK a greater chance to survey than they had before.